A comparative analysis on the in vivo toxicity of copper nanoparticles in three species of freshwater fish. (November 2015) - Song, Lan; Vijver, Martina G.; Peijnenburg, Willie J.G.M.; Galloway, Tamara S.; Tyler, Charles R.
Highlights: Comparative in vivo toxicity of nano-copper was studied in three fish species. Temperature can significantly affect the fate and toxicity of nano-copper in water. Copper ions were the main driver for the toxic effect of nano-copper. Nano-copper can cause damage to gill filaments and gill pavement cells. Physiological differences affect the sensitivity of fish species to nano-copper. Abstract: Copper nanoparticles (CuNPs) are used extensively in a wide range of products and the potential for toxicological impacts in the aquatic environment is of high concern. In this study, the fate and the acute toxicity of spherical 50 nm copper nanoparticles was assessed in juvenile rainbow trout ( Oncorhynchus mykiss ), fathead minnow ( Pimephales promelas ) and zebrafish ( Danio rerio ) for in vivo aqueous exposures following standardized OECD 203 guideline tests. The fate of the CuNPs in the aqueous media was temperature dependent. At the higher study temperature (26 ± 1 °C), there was both an enhanced particle aggregation and higher rate of dissolution compared with that at the lower study temperature (15 ± 1 °C). 96 h LC50 s of the CuNPs were 0.68 ± 0.15, 0.28 ± 0.04 and 0.22 ± 0.08 mg Cu/L for rainbow trout, fathead minnow and zebrafish, respectively. The 96 h lowest-observed-effect concentration (LOEC) for the CuNPs were 0.17, 0.023 and <0.023 mg/L for rainbow trout, fathead minnow, and zebrafish respectively, and are below the predicted environmental concentration of CuNPs for some aquatic environments suggesting a possible ecotoxicological risk to fish. Soluble copper was one of main drivers for the acute toxicity of the copper nanoparticles suspensions. Both CuNPs suspension and copper nitrate caused damage to gill filaments and gill pavement cells, with differences in sensitivity for these effects between the fish species studied. We show therefore common toxicological effects of CuNPs in different fish species but with differences in sensitivity with implications for hazard extrapolation between fish species.